Cordycepin Decreases Compound Action Potential Conduction of Frog Sciatic Nerve In Vitro Involving Ca2+-Dependent Mechanisms. (19th May 2015) - Yao, Li-Hua; Yu, Hui-Min; Xiong, Qiu-Ping; Sun, Wei; Xu, Yan-Liang; Meng, Wei; Li, Yu-Ping; Liu, Xin-Ping; Yuan, Chun-Hua
Abstract : Cordycepin has been widely used in oriental countries to maintain health and improve physical performance. Compound nerve action potential (CNAP), which is critical in signal conduction in the peripheral nervous system, is necessary to regulate physical performance, including motor system physiological and pathological processes. Therefore, regulatory effects of cordycepin on CNAP conduction should be elucidated. In this study, the conduction ability of CNAP in isolated frog sciatic nerves was investigated. Results revealed that cordycepin significantly decreased CNAP amplitude and conductive velocity in a reversible and concentration-dependent manner. At 50 mg/L cordycepin, CNAP amplitude and conductive velocity decreased by 62.18 ± 8.06% and 57.34% ± 6.14% compared with the control amplitude and conductive velocity, respectively. However, the depressive action of cordycepin on amplitude and conductive velocity was not observed in Ca 2+ -free medium or in the presence of Ca 2+ channel blockers (CdCl2 /LaCl3 ). Pretreatment with L-type Ca 2+ channel antagonist (nifedipine/deltiazem) also blocked cordycepin-induced responses; by contrast, T-type and P-type Ca 2+ channel antagonists (Ni 2+ ) failed to block such responses. Therefore, cordycepin decreased the conduction ability of CNAP in isolated frog sciatic nerves via L-type Ca 2+ channel-dependent mechanism.